A Distance-Learning Approach to Point-of-Care Ultrasound Training (ADAPT): A Multi-Institutional Educational Response During the COVID-19 Pandemic. (14th September 2021) - Nix, Kahra; Liu, E. Liang; Oh, Laura; Duanmu, Youyou; Fong, Tiffany; Ashenburg, Nicholas; Liu, Rachel B.
Abstract : Supplemental Digital Content is available in the text. Abstract : Problem: The COVID-19 pandemic significantly disrupted point-of-care ultrasound (POCUS) education. Medical schools and residency programs placed restrictions on bedside teaching and clinical scanning as part of risk mitigation. In response, POCUS faculty from 15 institutions nationwide collaborated on an alternative model of ultrasound education, A Distance-learning Approach to POCUS Training (ADAPT). Approach: ADAPT was repeated monthly from April 1 through June 30, 2020. It accommodated 70 learners, who included 1- to 4-week rotators and asynchronous learners. The curriculum included assigned prework and learning objectives covering 20 core POCUS topics. A rotating group of 30 faculty and fellows delivered daily virtual teaching sessions that included gamification to increase learner engagement and hands-on instruction through teleguidance. After participation, faculty and learners completed anonymous surveys. Outcomes: Educators reported a significant decrease in preparatory time (6.2 vs 3.1 hours per week, P < .001) dedicated to ultrasound education after implementing ADAPT. The majority of 29 learners who completed surveys felt "somewhat confident" or "very confident" in their ability to acquire (n = 25, 86.2%) and interpret (n = 27, 93.1%) ultrasound images after the intervention; the majority of 22 educators completing surveys rated the program "somewhat effective" or "very effective" at contributing to learner's ability to acquire (n = 13, 59.1%) and interpret (n = 20, 90.9%) images. Most learners (n = 28, 96.6%) and all educators (n = 22, 100%) were "satisfied" or "very satisfied" with ADAPT as a whole, and the large majority of educators were "very likely" (n = 18, 81.8%) to recommend continued use of this program. Next Steps: A virtual curriculum that pools the efforts of multiple institutions nationwide was implemented rapidly and effectively while satisfying educational expectations of both learners and faculty. This collaborative framework can be replicated and may be generalizable to other educational objectives.